PEMBELAJARAN PAI BERBASIS DARING: (Studi Tentang Inovasi Pendidikan dalam Mengelola Media Pembelajaran di SMP Baitul Aziz Tembung) - Ahmad Sukri Harahap; Nurul Hafizhoh; Agustian Agustian; Dinna Utami (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2020)
The purpose of this research was to describe educational innovation in managing instructional media in SMP Baitul Aziz Tembung. The formulation of the research problems are (1) Do teachers have educational innovations? and (2) What educational innovations are applied by teachers in managing learning media. The results of this study indicate that based on the description of the research results in the field, the authors can draw conclusions, namely: (1) Educational innovation using learning media is through video calls to see students' ability to understand the material being taught, showing videos to teach students to understand the material and especially wudhu and shalat. (2) Educational innovation through video and video calls carried out in groups and privately (3) Constraints experienced in teaching students through educational innovations using learning media are network problems, package problems, and understanding of the learning media used.